Deformation Study Of Darma Dam Using GPS Survey Method - Gumilar, Irwan; Z. Abidin, Hasanuddin; Andreas, H.; P. Sidiq, Teguh; Gamal, M.; Irsyam, M.; Sadisun, I.A. (Indonesian Journal of Geospatial, 2013)
Abstract. Darma Dam is located in the Village, District Kadugede, Kuningan regency, West Java, is a combination of the type heap dam (rockfill) and homogeneous soil deposits. Darma dam holds the potential disaster similar to the disaster Situ Gintung, Tangerang, which claimed hundreds of people. In fact, its potential is much more dangerous, if not anticipated. Darma dam is located in the hills, so that there is automatic in the area underneath paddies, plantations, and residential population that stretches from Kab. Kuningan, Kab. Cirebon, to Brebes, Central Java. Seeing the potential dangers posed by Darma then it should dam was monitored his activities as one of the main ways to mitigate catastrophic collapse of the dam. One of the main methods used to monitor the activity of the dam is deformation using methods that are used to monitor the deformation of the dam is with a survey method GPS (Global Positioning System). GPS surveys have been carried out for dam deformation monitoring Darma on December 9 to 10 May 2009 and 8 to 9 September 2009. GPS survey conducted in 19 point geodetic GPS receivers using two-frequency type. GPS survey detects horizontal and vertical deformation of the monitoring points around the dam Darma, in the order of a few mm in a period of about 5 months. Horizontal movements tend Dam Darma reservoir leads to the outside (away from the water), while for vertical shift seems not so clear (some point to decline (subsidence) and several point increase (uplift)). This study is expected to provide better information on the characteristics of dam deformation Darma. By understanding these characteristics, it can be analyzed potential catastrophic dam collapse Darma in this area and mitigation mechanisms can also be planned. Keywords : GPS, dams, deformationAbstract. Darma Dam is located in the Village, District Kadugede, Kuningan regency, West Java, is a combination of the type heap dam (rockfill) and homogeneous soil deposits. Darma dam holds the potential disaster similar to the disaster Situ Gintung, Tangerang, which claimed hundreds of people. In fact, its potential is much more dangerous, if not anticipated. Darma dam is located in the hills, so that there is automatic in the area underneath paddies, plantations, and residential population that stretches from Kab. Kuningan, Kab. Cirebon, to Brebes, Central Java. Seeing the potential dangers posed by Darma then it should dam was monitored his activities as one of the main ways to mitigate catastrophic collapse of the dam. One of the main methods used to monitor the activity of the dam is deformation using methods that are used to monitor the deformation of the dam is with a survey method GPS (Global Positioning System). GPS surveys have been carried out for dam deformation monitoring Darma on December 9 to 10 May 2009 and 8 to 9 September 2009. GPS survey conducted in 19 point geodetic GPS receivers using two-frequency type. GPS survey detects horizontal and vertical deformation of the monitoring points around the dam Darma, in the order of a few mm in a period of about 5 months. Horizontal movements tend Dam Darma reservoir leads to the outside (away from the water), while for vertical shift seems not so clear (some point to decline (subsidence) and several point increase (uplift)). This study is expected to provide better information on the characteristics of dam deformation Darma. By understanding these characteristics, it can be analyzed potential catastrophic dam collapse Darma in this area and mitigation mechanisms can also be planned. Keywords : GPS, dams, deformation